Rickard Hill Facies of the Schoharie Formation (Lower Devonian) Glacial Erratics from the Preakness Formation (Lower Jurassic) of High Mountain, Passaic County, New Jersey - Becker, Martin A.; Bartholomew, Alex (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2013)
Large fossiliferous glacial erratics occur scattered across the basalt of the Preakness Formation (Lower Jurassic) on High Mountain, Passaic County, New Jersey. These erratics are comprised of light tan to yellow, sandy limestone and contain fossiliferous beds with casts and molds of invertebrates. Analysis of these fossils including: rostroconchs, brachiopods, pelecypods, corals, bryozoans, nautiloid cephalopods and trilobites as well as the distinct lithology indicate that these erratics belong to the Lower Devonian Tristates Group and the Rickard Hill Facies of the Schoharie Formation. Outcrops of the Rickard Hill Facies of the Schoharie Formation occur in a narrow belt within the Helderberg Mountains Region of New York and due north of the High Mountain recovery location. Reconstruction of the glacial history across the Helderberg Mountains Region and New Jersey Piedmont indicates that the Rickard Hill Erratics have been transported tens of kilometers from their original source region during the Wisconsin glaciation. The Rickard Hill Erratics provide a unique opportunity to reconstruct additional elements of the complex surficial geology of the New Jersey Piedmont and High Mountain. Palynology of glacial kettle ponds adjacent to High Mountain along with cosmogenic-nuclide exposure studies on glacial erratics and the regional lake varve record indicate that the final deposition of the Rickard Hill Erratics occurred within a few thousand years after 18,500 YBP.